2012
DOI: 10.1002/hyp.9331
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modeling as a decision‐aiding tool for groundwater management in a Mediterranean agricultural watershed

Abstract: A decision‐aiding methodology for agricultural groundwater management is presented; it is based on the combination of a watershed model, a groundwater flow model, and an optimization model. This methodology was applied to an agricultural watershed in northeastern Greece. The watershed model used was the Soil and Water Assessment Tool (SWAT), which provided recharge rates for the aquifers. These recharge rates were imported in the well‐known MODFLOW groundwater flow model. Both models were calibrated and verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…The last decades, the intensive agricultural activities developed in the study area, have resulted in the construction of more than 500 groundwater wells used for irrigation of about 70 km 2 of agricultural land. The hydrogeological conditions and a conceptualization of this aquifer system were presented by Pisinaras et al (2013), who also indicated the high heterogeneity of the aquifer system and the relatively clear seasonal pattern of groundwater level fluctuation. The critical lateral inflows of water with high salt content from the southeastern part of the study area are also a fact.…”
Section: Study Area Descriptionmentioning
confidence: 98%
See 3 more Smart Citations
“…The last decades, the intensive agricultural activities developed in the study area, have resulted in the construction of more than 500 groundwater wells used for irrigation of about 70 km 2 of agricultural land. The hydrogeological conditions and a conceptualization of this aquifer system were presented by Pisinaras et al (2013), who also indicated the high heterogeneity of the aquifer system and the relatively clear seasonal pattern of groundwater level fluctuation. The critical lateral inflows of water with high salt content from the southeastern part of the study area are also a fact.…”
Section: Study Area Descriptionmentioning
confidence: 98%
“…According to Pisinaras et al, (2013), the major groundwater sink for the study area aquifer are the abstractions of groundwater for the satisfaction of irrigation needs. Corn is the dominant crop in the study area, covering 49% of the agricultural land, followed by wheat and cotton, which cover 24.5% and 11.5%, respectively.…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unconsolidated aquifer system of R. Kosynthos involves three main geological formations (Pliakas, 1998): (i) the upper formation, 8-80 m in thickness, of low permeability, consisting of clayey sand which interchanges at certain locations with gravel sand of small thickness, (ii) the intermediate aquifer formation, 10-70 m in thickness, consisting of permeable gravel sand, considered as a shallow confined aquifer, in some locations changing to semi-confined aquifer, (iii) the lower impermeable formation consisting of clayey silt in depth of 30-90 m. In the past, a series of artificial recharge application took place (Pliakas et al, 2005) as a countermeasure to overexploitation conditions for irrigation purposes, while the groundwater flow models were developed to investigate future scenarios for the optimization of the aquifer system in question (Pliakas et al, 2005;Pisinaras et al, 2013).…”
Section: Granular Aquifer System Of R Kosynthosmentioning
confidence: 99%